Changes in national rates of psychiatric beds and incarceration in Central Eastern Europe and Central Asia from 1990-2019: A retrospective database analysis - Adrian P Mundt; Enzo Rozas Serri; Mathias Siebenförcher; Valbona Alikaj; Fuad Ismayilov; Yury E Razvodovsky; Mevludin Hasanovic; Petar Marinov; Tanja Frančišković; Pavla Cermakova; Jaanus Harro; Lela Sulaberidze; et al. (Elsevier, 2021)
Background: Numbers of psychiatric beds (general, forensic, and residential) and prison populations have been considered to be indicators of institutionalisation of people with mental illnesses. The present study aimed to assess changes of those indicators across Central Eastern Europe and Central Asia (CEECA) over the last three decades to capture how care has developed during that historical period. Methods: We retrospectively obtained data on numbers of psychiatric beds and prison populations from 30 countries in CEECA between 1990 and 2019. We calculated the median of the percent changes between the first and last available data points for all CEECA and for groups of countries based on former political alliances and income levels. Findings: Primary national data were retrieved from 25 out of 30 countries. Data from international registries were used for the remaining five countries. For all of CEECA, the median decrease of the general psychiatric bed rates was 33•8% between 1990 and 2019. Median increases were observed for forensic psychiatric beds (24•7%), residential facility beds (12•0%), and for prison populations (36•0%). Greater reductions of rates of psychiatric beds were observed in countries with lower per capita income as well as in countries that were formerly part of the Soviet Union. Seventeen out of 30 countries showed inverse trends for general psychiatric beds and prison populations over time, indicating a possible shift of institutionalisation towards correctional settings. Interpretation: Most countries had decreased rates of general psychiatric beds, while there was an increase of forensic capacities. There was an increase in incarceration rates in a majority of countries. The large variation of changes underlines the need for policies that are informed by data and by comparisons across countries. Funding: Agencia Nacional de Investigación y Desarrollo in Chile, grant scheme FONDECYT Regular, grant number 1190613.